Comparison of Freelite and N-Latex serum free light chain assays : a critical review - Daves, Massimo (Array, 2021)
The measurement of serum free light chain (FLC) represents a fundamental aspect on the assessment of patients with monoclonal gammopathies (MG). Different analytical methods for FLC have become available with the possibility to obtain different value with a substantial impact on the assessment of patients with MG. This study aimed to evaluate FLC results obtained with two different assays and how the difference value obtained can impact in the patient"s assessment. Ninety-three patient serum samples that underwent analysis for FLC with two different methods, Serum Freelite (The Binding Site, Birmingham, UK) and N-Latex FLC (Siemens, Marburg, Germany), were included in this retrospective study. Statistical analysis was performed to evaluate correlation, difference, and the grade of concordance between the results obtained with the two methods. Significant statistical differences between the results obtained from the two methods were found (P <0.05). A good correlation was found (0.99 for κ FLC, 0.95 for λ FLC, and 0.94 for the κ/λ ratio, respectively). We found a weighted kappa value of 0.65 for κ/λ ratio, 0.65 for λ FLC and 0.90 for κ FLC. A positive bias found with the Bland-Altman plot mirrors overestimation of κ FLC and κ/λ ratio with Freelite compared to N-Latex, whilst a negative bias underscores underestimation of λ FLC by Freelite compared to N-Latex. Although in general the concordance between Freelite and N-Latex appears satisfactory, several discrepancies could be evidenced and consequently the two assays are not interchangeable.